2020
DOI: 10.3389/fgene.2020.529421
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Sucrose Diet Affects Phenotype Outcome in Adult Male Offspring: Role of Zbtb16

Abstract: Overnutrition in pregnancy and lactation affects fetal and early postnatal development, which can result in metabolic disorders in adulthood. We tested a hypothesis that variation of the Zbtb16 gene, a significant energy metabolism regulator, modulates the effect of maternal high-sucrose diet (HSD) on metabolic and transcriptomic profiles of the offspring. We used the spontaneously hypertensive rat (SHR) strain and a minimal congenic rat strain SHR- Zbtb16 , carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This is very interesting with regard to the previous observation that dexamethasone-induced mineralization is more intense compared to BMP2-treated DFCs [ 13 ]. The transcription factor ZBTB16, whose expression is highly induced by dexamethasone [ 11 ], might play a role for this difference as it is also related to energy metabolism [ 51 ]. A study on rabbit MSCs could further show that the lipidome changes during osteogenic differentiation of precursor cells and, moreover, that lipidomes are similar in cells from different origins [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is very interesting with regard to the previous observation that dexamethasone-induced mineralization is more intense compared to BMP2-treated DFCs [ 13 ]. The transcription factor ZBTB16, whose expression is highly induced by dexamethasone [ 11 ], might play a role for this difference as it is also related to energy metabolism [ 51 ]. A study on rabbit MSCs could further show that the lipidome changes during osteogenic differentiation of precursor cells and, moreover, that lipidomes are similar in cells from different origins [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…S6B ): Zbtb16 and Slc26a8 are also found to be involved in induction of mitochondrial metabolism and uncoupling capacity. Zbtb16 is a significant energy metabolism modulator and overexpression of the gene has been found to induce thermogenic programming including induction of mitochondrial fatty acid oxidation and uncoupling/electron transport chain [ 50 , 51 ]. The Slc26a8 gene is known to stimulate anion transport activity of the cystic fibrosis transmembrane conductance regulator (CFTR) which in turn facilitates ATP synthesis, ATP transport, and influences energy expenditure by regulating nutrient absorption and digestion [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…de Almeida-Faria et al ( 106 ) also found that feeding an obesogenic diet after weaning resulted in increased IRS-1 degradation, which suggests that exposure to obese individuals in utero combined with a postweaning obesogenic diet could significantly increase the risk of T2D. Moreover, the expression of miR-126 also changed in brown fat deposition and lipid metabolism of adult male offspring exposed to maternal high-sucrose diet ( 107 ). The reasons for this was unclear, but probably due to variation in the Zbtb16 gene ( 107 ).…”
Section: Role Of Mirnas In Glucose Metabolism In Offspringmentioning
confidence: 99%
“…Moreover, the expression of miR-126 also changed in brown fat deposition and lipid metabolism of adult male offspring exposed to maternal high-sucrose diet ( 107 ). The reasons for this was unclear, but probably due to variation in the Zbtb16 gene ( 107 ).…”
Section: Role Of Mirnas In Glucose Metabolism In Offspringmentioning
confidence: 99%